2016
DOI: 10.1016/j.cortex.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional connectivity in lesional peduncular hallucinosis with REM sleep behavior disorder

Abstract: Brainstem lesions causing peduncular hallucinosis (PH) produce vivid visual hallucinations occasionally accompanied by sleep disorders. Overlapping brainstem regions modulate visual pathways and REM sleep functions via gating of thalamocortical networks. A 66-year-old man with paroxysmal atrial fibrillation developed abrupt-onset complex visual hallucinations with preserved insight and violent dream enactment behavior. Brain MRI showed restricted diffusion in the left rostrodorsal pons suggestive of an acute i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 77 publications
0
17
0
2
Order By: Relevance
“…Dysfunction of the PPN relates to visual hallucination (VH) [ 15 ]. A resting-state functional connectivity MRI (rs-fcMRI) study in RBD patient showed reduced connection between lateral geniculate nuclei LGN and visual association cortex [ 18 ]. PD patients with probable RBD showed smaller volumes than patients without RBD and than healthy controls in the pontomesencephalic tegmentum where cholinergic, GABAergic and glutamatergic neurons are located.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of the PPN relates to visual hallucination (VH) [ 15 ]. A resting-state functional connectivity MRI (rs-fcMRI) study in RBD patient showed reduced connection between lateral geniculate nuclei LGN and visual association cortex [ 18 ]. PD patients with probable RBD showed smaller volumes than patients without RBD and than healthy controls in the pontomesencephalic tegmentum where cholinergic, GABAergic and glutamatergic neurons are located.…”
Section: Discussionmentioning
confidence: 99%
“…This formulation has much in common with the Kalman Filter approach to predictive learning that can embody statistical reliabilities and uncertainty and employs noradrenaline and acetylcholine to do as such (Dayan et al, 2000). These neurotransmitters may be opponent (Yu and Dayan, 2005) and have recently been implicated in the genesis of hallucinations (Collerton et al, 2005; Geddes et al, 2016). Kersten et al (2004) further characterise a generative model as ‘strong’ if samples can be produced from it that consistently look like the data it learned from (Kersten et al, 2004).…”
Section: The Future: the Emergence Of Computational Psychiatrymentioning
confidence: 99%
“…Geddes and colleagues describe visual peduncular hallucinosis in a 66-year-old man following an ischemic stroke in the left pons, encompassing locus coeruleus (LC) (70). They found that functional connectivity between the LC and visual association cortex was reduced in the hallucinating patient.…”
Section: Introductionmentioning
confidence: 99%